Jurnalisme: Harapan dan Tantangan di Era Revolusi Industri 4.0 dalam Mendidik Masyarakat - M. Yoserizal Saragih (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2018)
This article reviews journalism and digital media in the era of the industrial revolution 4.0 which are currently being discussed. Advances in Internet technology have opened wider opportunities for the media to utilize technology in the industrial revolution era 4.0 and at the same time begin to change as digital media by reconstructing editorial policies, media organizations, media management, human resources to target audiences in the media. new. Facing this period of 4.0 is not behind the world of journalists and the press who must keep abreast of developments, so as not far behind other industries. The concept of industrial revolution era journalism 4.0, which was formulated as news that reported all events or events, changed to a news concept that reported at the same time that events took place that had a high rate of speed. Journalism in the face of the 4.0 press industry revolution remains on the principles of journalistic ethics. When presenting news in a multi-directional media, it is not only unidirectional, but comprehensive. Through new media that is so fast in getting information. New media is currently very diverse in form and content. However, the task of HR which is engaged in journalism must make the news industry healthy by strengthening quality content and promoting truth. The development of digital journalism today which has been present in the midst of the wider community.